Nutrient accumulation and remobilization in relation to yield formation at high planting density in maize hybrids with different senescent characters. Issue 4 (21st March 2021) - Shao, Hui; Shi, Dongfeng; Shi, Wenjun; Ban, Xiangben; Chen, Yachao; Ren, Wei; Chen, Fanjun; Mi, Guohua
ABSTRACT: To test the hypothesis that plants could remobilize more nutrients from vegetative organs to fulfill the requirement of grain formation under high planting density, eight maize cultivars with different leaf senescence characters were chosen to study the relationship between stay-green character, nutrient (N, P, K) accumulation, post-silking nutrient remobilization and grain yield under three planting densities (60, 000, 75, 000, and 90, 000 plants per ha) in 2 years. We found that increased plant density aggravated leaf senescence, reduced concentration of N, P and K in all organs, reduced post-silking N, P, K accumulation per ha, increased nutrient remobilized efficiency. Stay-green degree was positively correlated to yield reduction at high planting density (R 2 = 0.35, P < 0.01), and negatively correlated to grain yield across planting densities and experimental years. Grain yield reduction at high planting density was negatively correlated to N (R 2 = 0.29, P < 0.01), P (R 2 = 0.51, P < 0.01), K (R 2 = 0.17, P < 0.05) remobilization efficiency. Thus, we conclude that efficient nutrient remobilization is important for achieving higher yield at high planting density. Stay-green too much may not be a favorable trait for high-yield breeding at high planting density.